Safeguarding Zoning and Vulnerability in Ahvaz City from the Passive Defense Perspective - Sohrab Amirian; Masoud Safaeipour; Hassan Hosseini Amini; hossein ebadi (تحقیقات کاربردی علوم جغرافیایی)
Vulnerability can be considered as an inherent defect in particular dimensions of the urban environment that is susceptible to damage due to its biological and physical characteristics or design features. Therefore, the present study aimed to investigate Ahwaz city structures and fine-tune its vulnerability from a passive defense perspective and to move it towards the future prospects of a safe city. This research is applied in terms of purpose and in terms of descriptive-analytical methodology based on the spatial-model studies approach. The data of this study include 11 educational, fire, administrative, police, power lines, terminals, urban facilities, business centers, roads, urban industries, gas transmission centers and health centers. GIS software was used to analyze the research data. Therefore, distance maps were designed and standardized for measuring the neighboring pattern after identifying the effective layers in the vulnerability and using the Distance tool. The FUZZY OVERLAY tool in ArcGIS software was used for spatial distribution and micro-zoning of Ahwaz vulnerability. The results show that in the section of vulnerability zoning, 29.73% of the city area is completely vulnerable, 29% vulnerable, 21.18% moderate, 13.22% low and 6.85% of the total city area in the state of vulnerability, respectively. There is very little reception.